Ground improvement and geosynthetics : proceedings of sessions of GeoShanghai 2010, June 3-5, 2010, Shanghai, China - Puppala, Anand J. (Geotechnical special publication, 2010)
Proceedings of sessions of GeoShanghai 2010, held in Shanghai, China, June 3-5, 2010. This Geotechnical Special Publication contains 48 papers presenting the most current research on ground improvement and geosynthetics. Topics include: ground improvement, especially with regard to unstable ground; soft soils; expansive soils; collapsible soils; reclaimed soils; contaminated soils; and others. Papers analyze improvement methods including mechanical and hydraulic methods, chemical stabilization methods in both shallow and deep ground, and reinforcement methods using geosynthetics. --